2021
DOI: 10.1002/anie.202105789
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Ultraviolet Nonlinear‐Optical van‐der‐Waals Beryllium Borates**

Abstract: Van-der-Waals (vdW) deep-ultraviolet (DUV) nonlinear-optical (NLO) materials hold great potential to extend DUV NLO applications to two dimensions,but they are rare in nature.I nt his study,w ep ropose ad esign principle to realize vdW DUV NLO materials via structural evolution from the non-vdW (BO 3 )-(BeO 3 F) layers in KBe 2 BO 3 F 2 (KBBF) to the vdW (BO 3 )-(BeO 4 H) layers in berborite Be 2 BO 5 H 3 (BBH) and the vdW (BO 4 )-(BeO 4 )l ayers in beryllium metaborate BeB 2 O 4 (BEBO). Based on first-princi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The third section involves heteroleptic tetrahedra POS­(NH 2 ) 2 , PO 2 S­(NH 2 ), GeO 3 (NH 2 ), GeS 3 (OH), and GeS 2 (OH) 2 , and they all demonstrate wide HOMO-LUMO energy gaps. It has been suggested that utilization of the monomers OH in hydroxyborates , and NH 2 (anisotropic tetrahedron SO 3 (NH 2 ) in M­(NH 2 SO 3 ) 2 (M = Sr, Ba)) is beneficial to the blue shift of the band gaps. Compounds containing the five heteroleptic tetrahedra are NH 4 POS­(NH 2 ) 2 , (NH 4 ) 2 PO 2 S­(NH 2 ), K 3 GeO 3 (NH 2 ), K 3 (H 2 O)­GeS 3 (OH), and Na 2 GeS 2 (OH) 2 (H 2 O) 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The third section involves heteroleptic tetrahedra POS­(NH 2 ) 2 , PO 2 S­(NH 2 ), GeO 3 (NH 2 ), GeS 3 (OH), and GeS 2 (OH) 2 , and they all demonstrate wide HOMO-LUMO energy gaps. It has been suggested that utilization of the monomers OH in hydroxyborates , and NH 2 (anisotropic tetrahedron SO 3 (NH 2 ) in M­(NH 2 SO 3 ) 2 (M = Sr, Ba)) is beneficial to the blue shift of the band gaps. Compounds containing the five heteroleptic tetrahedra are NH 4 POS­(NH 2 ) 2 , (NH 4 ) 2 PO 2 S­(NH 2 ), K 3 GeO 3 (NH 2 ), K 3 (H 2 O)­GeS 3 (OH), and Na 2 GeS 2 (OH) 2 (H 2 O) 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Theh ydrogen and/or fluorine in [B 3 O 3 F 2 (OH) 2 ]a nd [B(OH) 3 ]u nits make all the planar moieties to parallel extending the (011) plane.T he hydrogen-bonding interaction is acrucial factor defining the unique structure and property,w hich has also been verified in some previous literatures. [13] More importantly,N a-centered polyhedra act as linkers and pillar-like roles in layers and interlayers,r espectively.I nt he coordination sphere of Na atoms,t hree equatorial Oa toms come from one [B(OH) 3 ] and two [B 3 O 3 F 2 (OH) 2 ]u nits and residual Fa toms in equatorial position belong to the same [B 3 O 3 F 2 (OH) 2 ]u nit (Figure 1e). As for two polar Fatoms,their relative benzenelike [B 3 O 3 F 2 (OH) 2 ]u nits locate in different layers;t hese antiparallel pseudo layers (regarded as Aa nd A')f urther pack and finally form a-AA'AA'-packing mode (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, another design strategy to eliminate the A-site cations, i.e., via van der Waals (vdW) connection, has been proposed, and a series of possible DUV NLO structures have been accordingly predicted 68 , 73 , 75 , 78 , 81 . Among them, an existing berborite (Be 2 BO 5 H 3 , BBH) mineral as shown in Fig.…”
Section: First-principles Exploration Of New Duv Nlo Crystalsmentioning
confidence: 99%
“…Among them, an existing berborite (Be 2 BO 5 H 3 , BBH) mineral as shown in Fig. 2h can theoretically achieve DUV NLO performance comparable to KBBF 73 . The vdW DUV NLO crystal, firstly proposed by our group, holds great potential to extend the DUV NLO applications with higher output power and shorter output wavelength.…”
Section: First-principles Exploration Of New Duv Nlo Crystalsmentioning
confidence: 99%